Clinical characteristics and HPV type in recurrent respiratory papillomatosis in Colombia (2013)
ABSTRACT: Objective. Describe factors associated with aggressive forms of recurrent respiratory papillomatosis (RRP). Materials and methods. One hundred eighty-nine RRP cases diagnosed between 1985 and 2009 were identified in pathological records. HPV was detected by the SPF-10 method with broad spectrum primers, (version 1). Results. 113 patients had only one surgery (less aggressive) and 76, two or more interventions (more aggressive). The likelihood of aggressive lesions decreased with increasing age at diagnosis and HPV-11 was associated with no significant increase in the risk of aggressiveness. Conclusions. The age at diagnosis was the main determinant of RRP aggressiveness.